Influence of Legal Traditions and Legal Culture on the Institution of Marriage Contracts and the Possibility of its Improvement: The Experience of Kazakhstan - Zhunussova, T.B. (Academic Journal of Interdisciplinary Studies, 2022)
Since the Republic of Kazakhstan gained independence, it developed market relations and established private property as the leading type of ownership. Such fundamental changes required corresponding changes in the system of law, including family law. However, such reforms often depend on the mindset, legal culture, and legal traditions that have developed in society. In Kazakhstan, the practice of concluding marriage contracts (which govern property relations between spouses) has not developed or been seriously limited. Thus, this sphere needs to be considered for further improvement. The study aims at determining the social and legal factors affecting the regulation of marital relations through the conclusion of marriage contracts in Kazakhstan. Based on an expert survey, the authors of the article have revealed both positive and negative aspects of concluding a marriage contract and considered the main reasons for a small number of such contracts concluded between citizens of Kazakhstan. There a marriage contract is a special extrajudicial way of settling property relations between spouses that may arise in the future, a means of protecting their property rights and exercising property obligations. However, this method of regulation and protection is resorted to families with a high-income level and great life experience and often in special life situations.
Keywords: legal culture; family law; marriage contract; spouses; property relations; non-property relations